(untitled) (European Journal of Teaching and Education, 2024)
Project-based learning engages students in the collaborative design of generating and seeking answers to questions. Students work independently and creatively, to plan, execute, and make necessary adjustments to produce high-quality work, while developing competent twenty-first-century skills. These skills include critical thinking, collaboration, creativity/innovation, and communication. This work presents a unique partnership between a physics faculty member, a librarian, and a physician in a project-based ultrasound course at a primarily undergraduate institution. Implementing project-based learning, students actively engaged with real-world and personally, meaningful problems. Information literacy skills, such as evaluating and synthesizing information, were also naturally incorporated throughout the completion of student projects. Students responded to general surveys, self-evaluations, peer evaluations, metacognitive surveys, reflections, and attitude tests to help instructors improve, calibrate, and assess the teaching method. Key findings indicate a 9% growth in students’ information literacy skills and increased engagement. Additionally, results suggest that students prefer project-based learning compared to traditional teaching. This article highlights the course approach, assessment tools, and student engagement and perception.